The Role of High School Freshman Grades, Socioeconomic Status, and School Location on College Enrollment (Journal of School Administration Research and Development, 2024)
Prior research underscores the pivotal role high school freshman grade-point averages (FGPA) play in college enrollment, with a focus predominantly on urban settings. This study broadens this perspective, employing a diverse Arkansas sample (n = 33,207), spanning rural, suburban, and urban high school students and filling a notable literature gap. Utilizing a logit analysis, we found that high school students with an A FGPA were 23% more likely to enroll in college than B FGPA peers. Those failing a course in their high school freshman year were 13% less likely to enroll in college. Among similar academic ability students, economically disadvantaged students were 15% less likely to enroll in college. Locale classifications showed no significant enrollment variations. We conclude that FGPA and socioeconomic status (SES) are stronger enrollment predictors than locale classifications, finishing with intervention recommendations for lower-SES students in exploring college options.